Measuring antisocial values and attitudes in justice-involved male youth: evaluating the psychometric properties of the pride in delinquency scale and the criminal sentiments scale-modified - Skillington, Tracey (Criminal justice and behavior, 2014)
The Risk-Need-Responsivity (RNR) framework for working with offenders has been well validated. Factors that contribute to reoffending within adult and youth forensic populations have been identified, including antisocial attitudes, but less is known about the measurement of this construct in youth. Thus, in the present study, the reliability and validity of criminal attitudes measures were examined in a sample of justice-involved male youth (N = 291). Two measures widely used with adult offenders were included in the present study: the Pride in Delinquency Scale (PID) and the Criminal Sentiments Scale?Modified (CSS-M). Both measures were found to be reliable and valid, and of importance, useful in the prediction of reoffending behavior (area under the curve = .70 and .69 respectively). These findings further support the use of the RNR framework in general with youthful offenders, and more specifically, the use of criminal attitudes measures with youth.